Internet addiction and physical and psychosocial behavior problems among rural secondary school students - GÜR, KAMER (WILEY, 2015)
The aim of this study was to determine secondary school students' levels of Internet addiction and the physical and psychosocial behavior problems they face while using the Internet. This descriptive study was conducted in three state secondary schools in a rural area in the western part of Turkey. This study's sample consisted of 549 students who agreed to participate, with the consent of their families, and who had an Internet connection at home. The data were evaluated using t-tests and variance analyses. In this study the students' score of Internet addiction was at medium level (mean addiction score 44.51 +/- 17.90). There were significant differences between the students' Internet addiction scores and the presence of physical behavior problems (going to bed late, skipping meals, eating meals in front of the computer) and psychosocial behavior problems (suffering from conditions such as restlessness, anger, heart palpitations, or tremors when they could not connect to the Internet, decreased relationships with family and friends, feelings of anger, arguing with parents, and finding life boring and empty without an Internet connection).
Keywords: Internet addiction; physical and psychosocial behavioral problems; students; Turkey; problematic Internet use; DEPRESSION; QUESTIONNAIRE; ADOLESCENTS